HIV and Human Security in South Africa - Bindenagel, Annamarie (My University, 2006)
“HIV and Human Security in South Africa” explores the multiple dimensions of a fascinating individual, medical, economic, political and social epidemic. Its main question, what are the responsibilities of individuals, business and government in providing human security in the face of HIV AND AIDS in South Africa? developed out of the author’s watch and work in various communities and corporations in South Africa. The premise of “HIV and Human Security in South Africa” is one of sanctity. The sanctity of an individual is based on an inherent worth and includes the means for the development of dignity of each medically, economically, politically and socially. This human sanctity then proposes the foundation of human security, the individual freedom, medical care, economic opportunity, political stability and social cohesion that allows the actualization of that human sanctity. Human security is a precondition of the development of dignity, as without its protection the former is not possible. As such, viral infection, economic inequity, political instability and social unrest are all among the dire threats to human security and therefore to human sanctity. HIV and AIDS is such a threat. In fact, though primarily a virus that infects and afflicts individuals, it is a pandemic affecting medical, economic, political and social arenas. The plight unleashed on human security and human sanctity by HIV AND AIDS is particularly acute in South Africa, the nation with the highest number of infected, and therefore affected, persons in the world. Caught between the local needs and global pressures to address the pandemic, South Africa is in dire straits to secure the medical treatment, economic growth, political will, and social support to contain and combat HIV AND AIDS. The various angles of this argument are illustrated by a number of critical actors: Professor Ruben Sher, the first doctor to identify and to treat the virus in South Africa; Dr Lynne Webber, virologist at Lancet Laboratories and particularly involved in the upcoming wave of anti-viral drug resistance and in HIV and AIDS as a security threat; Mr. Christopher Whitfield, General Manager of Lilly South Africa; Prof. Eric Buch, health policy specialist at the University of Pretoria and NEPAD; Ms. Gillian Gresak, HIV AND AIDS manager at AngloPlatinum; and Mr. Fanyana Shiburi, policy director in corporate affairs at DaimlerChrysler South Africa. Each of these individuals, alone and through their respective organizations, shed light on the links between HIV AND AIDS as an individual virus, as well as on the challenges and opportunities the pandemic poses to medical care, economic growth, political stability and society. Throughout, the HIV and AIDS epidemic emerges as a crisis of culpability and responsibility. In other words, it is and remains a virus of individual infection with a ripple effect of affliction. It therefore demands a response from individuals, medical personnel, economic actors, entrepreneurs and investors, political leaders and policy strategists, and social and community activists to address the range of needs that it inflicts. It is in addressing these needs that the critical components of human security come to the fore, in order to facilitate the development of dignity of human sanctity.
Student Number : 0420490D - MMPP dissertation - School of Commerce, Law and Management - Faculty of Public and Development Management
Keywords: HIV; human security; South Africa